Ross Sea Dissolved Organic Matter Optical Properties During an Austral Summer: Biophysical Influences - D’Sa, Eurico J.; Kim, Hyun-Cheol; Ha, Sun-Yong; Joshi, Ishan (Frontiers in Marine Science, 2021)
The Ross Sea, one of the most productive regions in the Southern Ocean, plays a significant role in deep water formation and carbon cycling. Dissolved organic carbon (DOC) concentrations and chromophoric dissolved organic matter (CDOM) absorption and fluorescence (FDOM) properties were studied in conjunction with biophysical properties during austral summer. Elevated values of both DOC (mean 47.825.70 M) and CDOM (absorption coefficient at 325 nm, acdom325: mean 0.310.18 m-1) observed in the upper shelf waters in the southwest (SW), north of the Ross Ice Shelf (RIS), the northwest and along a transect inward of the shelf break, suggested in situ production and accumulation linked to the productive spring/summer season. However, regional differences were observed in CDOM with acdom325 higher (0.630.19 m-1) and its spectral slope S275-295 lower (24.062.93 m-1) in the SW compared to other regions (0.250.08 m-1 and 28.922.67 m-1, respectively). Similarly, the specific UV absorption coefficient or SUVA254 determined at 254 nm was greater (1.850.55 m2 mg-1 C) compared to other regions (1.070.24 m2 mg-1 C), indicating CDOM of greater molecular weight and aromaticity in the SW. Phytoplankton absorption spectra indicated the shallow mixed layer of SW Ross Sea to be dominated by diatoms (e.g., Fragilariopsis spp.), a preferential food source for grazers such as the Antarctic krill, which in large numbers have been shown to enhance CDOM absorption, a likely source in the SW. Excitation-emission matrix (EEM) fluorescence combined with parallel factor analysis (PARAFAC) retrieved one protein-like and two humic-like FDOM fractions commonly observed in the global ocean. In contrast to acdom325 which was uncorrelated to DOC, we observed weak but significant positive correlations between the humic-like FDOM with salinity and DOC, high value of the biological index parameter BIX and an instance of increasing FDOM with depth at a location with sinking organic matter, suggesting autochthonous production of FDOM. The absorption budget showed a relatively higher contribution by CDOM (70.718.3 %) compared to phytoplankton (22.515.2 %) absorption coefficients at 443 nm with implications to ocean color remote sensing. This first study of DOM optical properties provides additional insights on carbon cycling in the Ross Sea.